2021
DOI: 10.1177/10892680211056318
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic-Racial Identity as a Source of Resilience and Resistance in the Context of Racism and Xenophobia

Abstract: How youth come to understand their social identities and their relation to others’ identities can have important implications for the future of our society. In this article, we focus on how ethnic-racial identities (ERI) can serve to promote (or hinder) collective well-being. We first describe the nature of change in ethnic-racial identities over the course of childhood and adolescence. We then delineate three pathways by which youths’ ERI can be a mechanism for productive intergroup relations and thereby coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 83 publications
0
25
0
Order By: Relevance
“…Yet, Latinx youth who are developing a sense of linked fate with POC who are not Latinx should not gloss over the unique manifestations of anti‐Black racism or anti‐Indigeneity for other communities marginalized by these forms of oppression. Rather, youth should be encouraged to recognize these groups’ unique experiences with white supremacy (Rivas‐Drake, Pinetta, et al., 2021; Rivas‐Drake, Rosario‐Ramos, et al., 2021). The recognition of similarities and differences in experiences with racial oppression is vital for the development of a critical analysis of racism and engagement in authentic anti‐racist action among Latinx youth.…”
Section: Critical Analysis Of Racism: a Key Ingredientmentioning
confidence: 99%
“…Yet, Latinx youth who are developing a sense of linked fate with POC who are not Latinx should not gloss over the unique manifestations of anti‐Black racism or anti‐Indigeneity for other communities marginalized by these forms of oppression. Rather, youth should be encouraged to recognize these groups’ unique experiences with white supremacy (Rivas‐Drake, Pinetta, et al., 2021; Rivas‐Drake, Rosario‐Ramos, et al., 2021). The recognition of similarities and differences in experiences with racial oppression is vital for the development of a critical analysis of racism and engagement in authentic anti‐racist action among Latinx youth.…”
Section: Critical Analysis Of Racism: a Key Ingredientmentioning
confidence: 99%
“…Scholars such as Vacca et al [ 78 ] and Tip et al [ 79 ] further noted the importance of social networks that people from marginalized migrant backgrounds develop and extend, both within ethnic communities and with members of the broader population, which provide access to resources for wellbeing. Others have suggested that more complexified understandings of identity development, which take into account the ways in which heritage or ethnic identities are affected by discrimination, and how complex identities may act as protective mechanisms, are required [ 55 , 80 ]. Our findings with this cohort of Australian refugee background youth were not dissimilar to those of minority youth in Canada, where the impact of cultural identity on resilience was significant [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ethnic identity development is more central and critical for young people from minoritized groups because of the need to understand themselves beyond the White majority and due to the systematic discrimination that is enacted upon them for being minorities (Phinney, 2006). It is important to note that ethnic identity development processes that involve exploration (i.e., learning about one’s background, history, traditions) have been shown to intensify the detrimental effects discrimination has on mental health indicators for some youth of color because it can increase their awareness of racism (Rivas-Drake et al, 2021; Yip et al, 2019). Yet, given the vast majority of research suggesting that ethnic identity promotes healthy development, experts have argued that having an increased sensitivity to racism may foster adaptive coping skills that are ultimately protective for young people in the long term (Rivas-Drake et al, 2021; Umaña-Taylor et al, 2014).…”
Section: Discussionmentioning
confidence: 99%